The antiparasitic potential of senna alata leaves extracts and fractions against marine parasitic leech zeylanicobdella arugamensis - Amanda Oya Jimmy; Venmathi Maran Balu Alagar; Rossita Shapawi; Nurzafirah Mazlan; Muhammad Dawood Shah (Penerbit UTM Press, 2024)
Aquaculture has been a rapidly growing industry in Malaysia, contributing to the country's gross domestic product and enhancing food security and employment opportunities. Among the marine species cultivated in Malaysia are sea bass, snapper, and grouper. Unfortunately, the marine parasitic leech Zeylanicobdella arugamensis is posing a major threat to a wide variety of cultured marine fish species, including grouper. Various veterinary drugs are used to control parasitic leeches, which are toxic to fish and humans. So, the development of natural treatments from plants is vital. In response to this, Senna alata, also known as the Ringworm bush, was selected. This study aims to evaluate the antiparasitic activity of S. alata methanol extracts, its fractions and water extract against Z. arugamensis. The adult and mature leeches were divided into control and treatment groups. The methanol extract, its fractions (including hexane, chloroform, ethyl acetate, and butanol), and water extracts of S. alata were obtained. Various concentrations (100, 50, 25 and 12.5 mg/ml) of the extracts and fractions were prepared in 5% DMSO and concurrent notation of physico-chemical parameters. Upon exposure, the behaviour and mortality time of the parasitic leeches were recorded. The exposure to the extracts and fractions induced behavioural changes in the parasitic leeches, characterised by aggressive and abnormal swimming patterns coupled with an inability to attach their suction to the surface. Ultimately, complete mortality of parasitic leeches was obtained across extracts and fractions. Overall, the aqueous extract proved to be the most effective, as it displayed the shortest mortality time recorded among the extracts and fractions (2.38±0.15 to 33.08±3.52 minutes). Consequently, the study highlights the antiparasitic potential of the extracts and fractions of S. alata against parasitic leech Z. arugamensis infestation.